OP0250 Distinct Imaging Patterns of Heart Failure in Systemic Lupus Erythematosus: Evaluation Using Cardiovascular Magnetic Resonance. (10th June 2014) - Mavrogeni, S.; Karabela, G.; Stavropoulos, E.; Plastiras, S.; Spiliotis, G.; Gialafos, E.; Kolovou, G.; Sfikakis, P.P.; Kitas, G.D.
Abstract : Background: Systemic lupus erythematosus (SLE) is associated with increased cardiovascular disease either due to disease per se or to non-SLE related causes. We hypothesized that cardiac tissue characterization by cardiovascular magnetic resonance (CMR) may aid in clarifying the pathophysiology of heart failure in SLE. Methods: Thirty-two SLE patients (29 women), aged 29±7 yrs (range 25-40), after recent X-Ray coronary angiography (<30 days), due to new-onset HF NYHA I-II, were consecutively evaluated by CMR, including LV function, STIR T2 and late gadolinium enhanced (LGE) images. Results: T2 ratio>2 and patchy, epi/endo-myocardial LGEs with a total extent of 7±2% LV, due to acute myocarditis, were identified in 5/31 (16%) patients. LV function impairment, but without inflammation or fibrosis, due to dilated cardiomyopathy (DCM), was also found in 5 other patients (16%). A transmural myocardial scar (6 inferior and 5 anteroseptal), due to myocardial infarction, was evident in other 11/32 patients (34%), with an extent of 25±3% LV. Notably, diffuse subendocardial fibrosis with an extent of 34±3% LV, due to vasculitis, was revealed in 9 patients (29%). Finally, aortic valve stenosis and mitral valve regurgitation, due to Libman- Sacks endocarditis, were diagnosed in the remaining 2 patients (6%). No mixed pathology was observed in any patient. The presence of LGE, denoting myocardial fibrosis, correlated significantly with longer disease duration, higher erythrocyte sedimentation rate and the presence of anti-phospholipid antibodies Abnormal X-Ray coronary angiography (3, 5 and 3 patients having 1, 2 and 3 vessel disease, respectively) was found only in those patients with transmural myocardial scar, which followed the distribution of diseased vessels. Conclusions: Heart failure in patients with SLE is due to various causes, including myocarditis, dilated cardiomyopathy, coronary artery disease, vasculitis and/or valvular disease. Assessment of the pathophysiologic background by CMR may facilitate the differential diagnosis and patients' risk stratification. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3774